2015
DOI: 10.1016/j.compositesb.2015.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional graphene nanoplatelets/cellulose nanocrystals composite paper

Abstract: We demonstrate a water-based method to fabricate strong, electrically and thermally conductive hybrid thin films (papers) made from the combination of graphene nanoplatelets (GnP) and cellulose nanocrystals (CNC). Unpressed and hot-pressed GnP papers containing CNC ranging from 0 wt% to 25 wt% were prepared. It is found that the GnP is well aligned within the hybrid paper, and a higher degree of alignment is induced by the hot-pressing process. The mechanical properties of the resulting papers increased with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 42 publications
4
26
0
Order By: Relevance
“…Figure 6 showed a layered structure laminated by graphene sheets in the cross-section of the membranes, and similarly observed morphology have been also demonstrated in previous study [ 15 , 26 , 29 ]. This was attributed to the binding action of GO and NFC, which embedded among the graphene flakes, gluing them together.…”
Section: Resultssupporting
confidence: 87%
“…Figure 6 showed a layered structure laminated by graphene sheets in the cross-section of the membranes, and similarly observed morphology have been also demonstrated in previous study [ 15 , 26 , 29 ]. This was attributed to the binding action of GO and NFC, which embedded among the graphene flakes, gluing them together.…”
Section: Resultssupporting
confidence: 87%
“…They found that by blending increasing amount of exfoliated graphite nanoplatelets with bacterial cellulose improved the electrical conductivity values, with 2 wt% of exfoliated graphite nanoplatelets in the bacterial cellulose matrix yielding an electrical conductivity value of approximately 0.75 S cm -1 . Similar work on improving the electrical, thermal and mechanical properties of graphene nanoplatelets/cellulose nanocrystals composite paper was also reported by Wang et al (2015). They found that they could still maintain a good-enough improvement in electrical conductivity using up to 15 wt% cellulose Cellulose nanocrystals in the graphene nanoplatelets hybrid paper.…”
Section: Introductionsupporting
confidence: 51%
“…SEM observations of the crease on the outside of a folded paper revealed a few microcracks on the EEG and A‐EEG paper, on the other hand, the P‐EEG paper showed smooth morphology, where the graphene layer was continuous and free from cracks across the crease (Figure S9c, Supporting Information). These results confirm that the graphene layer in P‐EEG paper could withstand rupture even upon folding, because mechanical compression could reduce the most pores and defects in the graphene paper, resulting in the enhancement of alignment and contact between the graphene sheets …”
Section: Resultssupporting
confidence: 66%